2012
DOI: 10.1093/ejcts/ezr106
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump transapical mitral valve replacement: evaluation after one month

Abstract: This study demonstrates adequate deployment and anchorage of a unique, repositionable mitral valved stent. A good valve function was revealed in animals observed for 4 weeks and in one pig after 8 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The cavity-to-pericardial (“leakage”) pressure gradient is lower for a RV free wall entry compared with LV free wall entry, and in this way our trajectory may enhance acute procedural safety of closed-chest direct cardiac access. Translated into patients, our approach would allow subxiphoid introduction of large appliances into the heart without surgery, for example transcatheter mitral valves having delivery systems 10 mm wide or more [17]. In this preclinical experience, we found that the entry tract across the interventricular septum recoiled completely, was associated with no early or late ventricular septal defect, was associated with no evident myocardial dysfunction or conduction abnormality, and left a small residual fibrotic scar with no evident bystander injury.…”
Section: Discussionmentioning
confidence: 99%
“…The cavity-to-pericardial (“leakage”) pressure gradient is lower for a RV free wall entry compared with LV free wall entry, and in this way our trajectory may enhance acute procedural safety of closed-chest direct cardiac access. Translated into patients, our approach would allow subxiphoid introduction of large appliances into the heart without surgery, for example transcatheter mitral valves having delivery systems 10 mm wide or more [17]. In this preclinical experience, we found that the entry tract across the interventricular septum recoiled completely, was associated with no early or late ventricular septal defect, was associated with no evident myocardial dysfunction or conduction abnormality, and left a small residual fibrotic scar with no evident bystander injury.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] During first studies, 30 pigs underwent off-pump mitral valved stent implantation with followup times of 60 minutes and 7 days. Accurate positioning was established in all but 5 animals.…”
Section: Preclinical Developmentmentioning
confidence: 99%
“…Gross evaluation revealed that 50% to 70% of the atrial element was covered by tissue growth at 4 to 8 weeks. 37 An additional study focused on the evaluation of 2 different frame designs: (1) the first design consisted of a circular crown-shaped atrial element connected to a tubeshaped ventricular element, and (2) in the second design, this atrial element was D-shaped to achieve better anatomic alignment. Although in vitro testing showed less PVL in the antero medial region in D-shaped design stents, animal tests showed less favorable results, with rotational reorientation of all stents with D-shaped elements causing more severe PVL and preventing these advantages to take effect.…”
Section: Preclinical Developmentmentioning
confidence: 99%
“…69 A subsequent bovine pericardial design with a unique ventricular tethering fixation system reduced embolization, and all animals with initially successful implants maintained normal hemodynamics and stability to 8 weeks. 70 Initial first-in-human temporary implants during surgical mitral valve replacement were performed in 2013.…”
Section: Fortismentioning
confidence: 99%